The Ghost of the Bermuda Triangle (You Choose Stories Scooby-Doo, ,, 2014)
In this You Choose mystery, Scooby Doo and the gang are on a cruise, right through the Bermuda Triangle! Suddenly, a ghost interrupts a costume contest, sending everyone running. Readers choose which characters to follow. Will your path lead to dangerous criminals, confused passengers, or a real ghost? Solve the mystery again and again!

The mystery of the maze monster (You choose. Scooby-Doo!, ,, 2014)
Scooby Doo and the gang are called to the mansion of Minos King to solve the mystery of the Minotaur in the garden maze--with the help of the reader.

The secret of the sea creature (You choose. Scooby-Doo!, ,, 2014)
A day at the beach turns into an adventure when Scooby Doo and the gang encounter a sea monster--and the reader's choices govern what happens next.

The Terror of the Bigfoot Beast (You Choose Stories Scooby-Doo, ,, 2014)
On a camping trip, Scooby-Doo and the Mystery Inc. gang encounter Bigfoot! Will the gang pack up or stay to investigate? Should they follow Bigfoot's trail or wait for help? Does Scooby get to chow down or go hungry? In this interactive story, YOU CHOOSE the path the gang should take. With your help, they'll solve this camp-out caper. A new series of You Choose Books featuring Scooby-Doo and his friends Fred, Velma, Daphne, and Shaggy! These mysteries feature fun, action-packed stories (and illustrations!) that allow the reader to choose their own path. In each book, with the help of the reader, Scooby and the gang will solve spooky mysteries and expose common criminals in a truly dynamic reading experience.